2015
DOI: 10.1016/j.vaccine.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of heterologous H5N1 influenza booster vaccination 6 or 18 months after primary vaccination in adults: A randomized controlled clinical trial

Abstract: Adults primed with a dose-sparing oil-in-water adjuvanted H5N1 subclade vaccine had rapid and durable antibody responses to a heterologous subclade boosting vaccine given 6 or 18 months later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The clinical trials included [25][26][27][28][29][30][31][32] and the number of participants is shown in Table 1. Demographic characteristics and prevaccination seropositivity for HI against the vaccine homologous virus and the A/H1N1pdm09 virus are shown in Supplementary Tables 1 and 2, respectively. ELISA Anti-H1 stalk antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical trials included [25][26][27][28][29][30][31][32] and the number of participants is shown in Table 1. Demographic characteristics and prevaccination seropositivity for HI against the vaccine homologous virus and the A/H1N1pdm09 virus are shown in Supplementary Tables 1 and 2, respectively. ELISA Anti-H1 stalk antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…6; Table 1; Supplementary Table 6). [25][26][27][28][29][30][31][32] We aimed to select approximately 30 participants from the relevant treatment groups of each trial. Participants were eligible for the present study if they had completed the clinical trial according to the protocol and had sufficient residual sample volume at all protocol-specified sample timepoints.…”
Section: Clinical Trials Participants and Vaccinesmentioning
confidence: 99%
“…Vaccine antigens are expensive to manufacture and there are limited manufacturing facilities for making vaccines to the required good manufacturing practice (GMP) standards. The addition of AS03 led to a similar response to a lower dose of H5N1 antigen (3.75μg) compared to the standard 15μg dose 29 .…”
Section: Dose Sparingmentioning
confidence: 89%
“…The rate of solicited AEs among MG1109 recipients was comparable to those from previous clinical trials of influenza vaccines, including both H5N1 monovalent and conventional trivalent influenza vaccines. [2][3][4][5][6] According to the meta-analysis of trials that assessed influenza H5N1 vaccine safety and immunogenicity, the rates of adverse events were reported variably: fever (0-8.7%), headache (8.3-46%), malaise (4-55%), myalgia (4-47%), local pain (14-89%) and erythema (0-42%). 7 In addition to the vaccine composition, the difference in the definition and severity threshold of adverse events might responsible for the wide range observed.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, priming with a clade-mismatched pandemic influenza A/H5N1 vaccine improved the rapidity and magnitude of the immunological response following a heterologous single-dose pandemic H5N1 vaccine. 3,12,13 In fact, it is impossible to accurately predict which clade/subclade of H5N1 will cause the next pandemic. Considering the possibility of cross-reactive immunogenicity, strategic priming with the pre-pandemic H5N1 influenza vaccine-not just vaccine stockpiling-is necessary as part of a pandemic preparedness plan.…”
Section: Discussionmentioning
confidence: 99%